1985
DOI: 10.1093/infdis/151.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Development and Persistence of Class-Specific Antibodies in the Serum and Nasopharyngeal Washings of Rubella Vaccinees

Abstract: Serial samples of serum and nasopharyngeal washings were obtained from 43 volunteers given one of four rubella vaccines (HPV77.DE5, RA27/3, To-336, and Cendehill) and from nine naturally infected volunteers. Rubella-specific serum IgG was detected by radioimmunoassay for up to 12 years in all but one vaccinee, and booster responses occurred in 23.3% of vaccinees. Rubella-specific serum IgA was detected in 37 (90.2%) of 41 vaccinees one year after vaccination but in only five (45.5%) of 11 vaccinees tested 10-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The present study suggests, in accord with others (O'Shea et al 1982(O'Shea et al ,1984(O'Shea et al ,1985, that antibody levels in vaccinated individuals are on average lower than those in naturally infected individuals; the mean concentrations in teenage and young adult females are lower than in males of the same age (Fig. 3).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study suggests, in accord with others (O'Shea et al 1982(O'Shea et al ,1984(O'Shea et al ,1985, that antibody levels in vaccinated individuals are on average lower than those in naturally infected individuals; the mean concentrations in teenage and young adult females are lower than in males of the same age (Fig. 3).…”
Section: Discussionsupporting
confidence: 91%
“…The degree of immunity to rubella infection provided by low concentrations of antibody is unclear. In the present study a low threshold (3-3 i.u./ml) was regarded as indicative of immunity since challenge studies have revealed that low levels of naturally acquired antibody confer immunity to reinfection (Mortimer et al 1981;O'Shea et al 1982O'Shea et al , 1983O'Shea et al , 1984O'Shea et al , 1985. However, it must be remembered that RH does not distinguish between antibody produced in response to natural infection and that produced in response to vaccination, and similar challenge studies suggest low levels of vaccine-induced antibody do not correlate well with protection from reinfection (Balfour et al 1981;Harcourt et al 1980).…”
Section: Discussionmentioning
confidence: 95%
“…Patients who have been persistently reactive for rubella-specific IgM at reasonable concentrations have been described infrequently [5,6], although persistent low concentrations have been described after immunization [17]. The four cases we describe were all investigated after contact with a case of presumed rubella.…”
Section: Resultsmentioning
confidence: 98%
“…3. Typically, for the individual, high-level specific JgG from a recent viral infection (or vaccination) rapidly decays over a period of a few months (often at different rates for each individual) to a level which is maintained for many years [18][19][20][21]. The profile illustrated in Fig.…”
Section: Serological Testmentioning
confidence: 99%